1999
DOI: 10.1254/jjp.79.131
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Angiotensin II Type 1 Receptor by TCV-116: Quantitation by In Vitro Autoradiography

Abstract: Inhibition of angiotensin (Ang) II type 1 (AT1) receptors in various target tissues of adult Sprague-Dawley rats was studied after single oral administration of TCV-116. The effects of TCV-116 on Ang II-receptor binding were assessed by quantitative in vitro autoradiography using 125I-[Sar1,Ile8]Ang II as a ligand. Four hours after the administration of TCV-116 (1 mg/kg), Ang II-receptor binding was markedly inhibited in the kidney (20% of control), adrenal cortex (27%), thoracic aorta (57%), heart (55%) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The central actions of angiotensin II appear to be mediated through the circumventricular organs such as the area postrema and subfornicular organ, which contain angiotensin II-sensitive neurons and which, lacking a blood-brain barrier, are accessible to circulating angiotensin II [6]. It is not known whether candesartan, or indeed any of the AT " receptor blockers, penetrates the blood-brain barrier in humans, although there is evidence of partial penetration into the central nervous system in rats at high doses [32,33]. Conversely, AT " receptor blockers do not reduce, and may even increase, circulating levels of angiotensin II [31], and require access to the AT " receptor to exert their effect.…”
Section: Discussionmentioning
confidence: 99%
“…The central actions of angiotensin II appear to be mediated through the circumventricular organs such as the area postrema and subfornicular organ, which contain angiotensin II-sensitive neurons and which, lacking a blood-brain barrier, are accessible to circulating angiotensin II [6]. It is not known whether candesartan, or indeed any of the AT " receptor blockers, penetrates the blood-brain barrier in humans, although there is evidence of partial penetration into the central nervous system in rats at high doses [32,33]. Conversely, AT " receptor blockers do not reduce, and may even increase, circulating levels of angiotensin II [31], and require access to the AT " receptor to exert their effect.…”
Section: Discussionmentioning
confidence: 99%
“…Candesartan, administered systemically by osmotic minipump (Nishimura et al, 2000) or orally (Song et al, 1999) . After chronic subcutaneous (but not acute i.v.)…”
Section: Penetration Into Brainmentioning
confidence: 99%
“…Because the RVLM area contains a moderate density of AT 1 receptors, 12,22,26 endogenous Ang II can stimulate RVLM neurons through AT 1 receptors. A quantitative autoradiographic study found that the nucleus tractus solitarius and the dorsal motor nucleus of the vagus possess a higher density of AT 1 receptors in adult SHR than in WKY, 28 suggesting the number of AT 1 receptors per neuron being increased in SHR compared with WKY.…”
Section: Matsuura Et Al Ang II and Candesartan To Rvlm Neurons 563mentioning
confidence: 99%